Technical use of intravascular ultrasound in chronic total occlusion percutaneous coronary interventions: insights from the Euro-CTO registry - Arioti, Manfredi; Moroni, Alice; Mashayekhi, Kambis; Werner, Gerald S; Agostoni, Pierfrancesco; Gorgulu, Sevket; Ayoub, Mohamed; Avran, Alexandre; Kalay, Nihat; Goktekin, Omer; Ladwiniec, Andrew; Zaczkiewicz, Myron; et al. (Springer, 2025)
Background: Intravascular ultrasound (IVUS) plays a central role in complex percutaneous coronary interventions (PCI). While guidance for stenting and optimization is the most common reason for IVUS use, the technical application of IVUS for greater procedural efficiency is becoming increasingly important. The impact of IVUS has been only partially investigated in its technical aspect. Methods: We analyzed 15,226 CTO-PCIs from the EuroCTO registry between January 2022 and December 2023. We compared CTO PCI procedures performed with or without IVUS and further categorized IVUS use based on its application (technical reasons or stent optimization). Results: IVUS was used in 22% (n = 3393) of cases and increased consistently from 12 to 24% between 2016 and 2023. Guidance for stenting and optimization remained the most common indication (86.4% of IVUS cases). Importantly, IVUS was utilized in 7.2% (n = 1092) of cases for technical reasons, mainly to identify the proximal cap (55.7% of technical indications, n = 608). IVUS-guided CTO-PCIs showed higher J-CTO scores (2.46 ± 1.20 vs. 2.19 ± 1.25; p < 0.001) and greater use of the retrograde approach (28% vs. 19%; p < 0.001). Technical success rates were comparable between the IVUS and angiographic groups (90% vs. 92%; p = ns). High-experience IVUS users achieved greater technical success compared to low- and intermediate-experience users (p < 0.010). On multivariable analysis, IVUS use was an independent predictor of technical success (odds ratio 1.39, 95% CI from 1.07 to 1.82, p value = 0.016). Conclusions: IVUS in CTO PCI is primarily used for stent optimization. However, there is an increasing use of IVUS for technical reasons resulting in similar technical success rates even in more complex lesions and standing out as an independent predictor of success. Experience seems to play a role, with an advantage for highly experienced users.